Retrospective Analysis: Infant Health Outcomes Born to Mother with Systemic Lupus Erythematosus - Nooryanto, Mukhammad; Wulandari (Asian Journal of Health Research, 2025)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune disease that affects young women and presents risks during pregnancy, potentially impacting infant health. This study analyzes infant health outcomes such as birth weight, APGAR score (AS), preterm birth, NICU admission, and mortality in infants born to mothers with SLE. Material and Methods: A retrospective analysis was performed on data from infants born to mothers with SLE between 2023–2025. Data were analyzed using descriptive, bivariate, and multivariate tests with p < 0.05 considered significant. The study was conducted at General Hospital Dr. Saiful Anwar. Results: Of the subjects, 78.57% had mild SLE, 14.28% had moderate SLE, and 7.15% had severe SLE. Significant associations were found between pregnancy status and SLE severity (p = 0.000), delivery method (p = 0.005), blood loss (p = 0.035), birth weight (p = 0.022), and APGAR score (p = 0.005). Cesarean sections were more common in mild to moderate SLE cases. NICU admission was significantly associated with SLE severity (p = 0.002), and fetal mortality was higher in severe SLE cases (p = 0.001). The R-square values for the variables showed that 61.9% of the variation in Apgar score, 73.3% in blood loss, and 73.6% in mortality were explained by factors such as blood loss, grade of SLE, gravida, MEX SLEDAI, maternal age, and mode of delivery. Conclusion: SLE severity significantly influences maternal and neonatal outcomes, including delivery method, blood loss, birth weight, and APGAR score.